An Analysis of the Effectiveness of International Human Rights Instruments in Protecting the Rights of Migrant Workers - P.K, Venkateswaran; Phillipose, Geni (Journal of Neonatal Surgery, 2025)
Migrant workers constitute a significant portion of the global labor force, often filling labor gaps in both developed and developing countries. Despite their critical contributions to host economies, migrant workers frequently face systemic discrimination, exploitation, and limited access to legal protections. This study seeks to analyze the effectiveness of international human rights instruments in safeguarding the rights of migrant workers, focusing on key frameworks such as the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICMW), the International Labour Organization (ILO) Conventions, and the Universal Declaration of Human Rights (UDHR). Through a qualitative and comparative approach, this study explores how various states incorporate international legal norms into their domestic legislation, the challenges of ratification and enforcement, and the role of international monitoring bodies. Particular attention is given to the gap between ratification and implementation, highlighting how political, economic, and social factors affect the practical realization of migrant workers' rights. Case studies from regions with high levels of labor migration such as the Gulf Cooperation Council (GCC) countries, the European Union, and South-East Asia are examined to assess how well these international instruments are being operationalized on the ground. The study also evaluates the effectiveness of soft law instruments and multilateral cooperation in promoting accountability and improving working conditions for migrants. Furthermore, it considers the emerging global trends in migration governance, including the Global Compact for Safe, Orderly and Regular Migration, and how they interact with established legal protections. Findings suggest that while international human rights instruments provide a comprehensive legal foundation for the protection of migrant workers, enforcement remains weak due to lack of political will, inadequate legal infrastructure, and insufficient international oversight. The study concludes with policy recommendations aimed at enhancing the international legal regime for migrant workers and strengthening compliance mechanisms.